Examining The Impact Of Service Quality, Company Image, And Customer Loyalty On Customer Interest In Refinancing: A Multiple Regression Approach - Yeyet Daryati (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — This Research aims to determine the effect of service quality, company image on the interest in submission of customer refinancing with customer loyalty moderating variables. The population used in this study is customers at Bank BNI KCP Majalengka with a total of 2455 customers, while the sample taken is 100 respondents.Research method— This Research aims to determine the effect of service quality, company image on the interest in submission of customer refinancing with customer loyalty moderating variables. The population used in this study is customers at Bank BNI KCP Majalengka with a total of 2455 customers, while the sample taken is 100 respondents.Result— Based on simultaneous regression testing, it was found that the variable quality of service (X1), Company Image (X2) and moderating variable, namely customer loyalty variable (X3) had a significant effect on variable Interest in Submission of Customer Refinancing (Y). This can be seen from the significance value of 0.000 <(α = 0.05), so that stated H0 is rejected and the three variables X have a significant effect on variable Y. Meanwhile, to measure the accuracy of multiple regression models, it can be seen from the coefficient of determination (Adjusted R -Square)Conclusion— This study has an Adjusted R-Square value of 0.472. This shows that service quality variables, company image and customer loyalty in influencing interest in customer refinancing submission is 47.2% while the remaining 52.8% interest in the customer refinancing proposal can be influenced by other variables not included in the analysis model of this study